Effect of Freezing State Change on the Quality of Frozen Blueberry Fruits - LI Yang, CHEN Longjiao, ZHENG Ziyi, HUANG Bifei, YU Miao (Shipin Kexue)
Frozen ‘Beicun’ blueberry fruits were classified based on three key temperatures: the glass transition temperature (Tg’) at their maximum cryo-concentration, the intersection temperature (Tg”) between the freezing curve and the glass transition temperature curve, and the characteristic freezing endpoint temperature (Tm’) into three states: rubbery (T > Tm’), partially frozen concentrated (Tg” Tm’), partially frozen concentrated (−40 ℃, Tg” Tm’), partially frozen concentrated (−40 ℃, Tg” < T < Tm’), or lower glassy state temperature (−50 ℃, Tg’ < T < Tg”; −60 ℃, T < Tg’). Besides, a control group was set up without any temperature changes. Juice loss, hardness, nutrient contents, membrane integrity, and enzyme activities were determined to explore the effects of different freezing states and state changes on the quality of frozen blueberry fruits. The results indicated that frozen blueberry fruits in the glassy state exhibited the best quality. State transitions resulted in more pronounced quality deterioration in blueberry fruits; greater temperature changes led to higher juice loss, hardness reduction and nutrient loss, more serious cell integrity damage, and higher activities of peroxidase and polyphenol oxidase. Therefore, glassy state freezing (at temperatures below Tg’) could better maintain the quality of blueberry fruits; however, it is crucial to avoid state transitions caused by temperature fluctuations during frozen storage.